The war that made the Roman Empire : Antony, Cleopatra, and Octavian at Actium - Strauss, Barry S. (Simon & Schuster, 2022)
"The story of one of history's most decisive and yet little known battles, the Battle of Actium in 31 BC, which brought together Antony and Cleopatra on one side and Octavian, soon to be emperor Augustus, on the other, and whose outcome determined the future of the Roman Empire"--